Brooks and Dunn [videorecording (DVD)] (A&E Television Networks : Distributed by New Video, 2008)
Leon Eric Brooks, a Louisiana native, performed at ski resorts in Maine before moving to Nashville to become a songwriter. Ronnie Gene Dunn, a Texas native, attended a conservative Christian university, but was kicked out for playing music on the side. Learn how these two very dfferent musicians were eventually brought together by Arista Records executive Tim DuBois, and how their vibrant mix of hard-charging country, potent emotions, and serious swagger helped their first album sell more than six million copies.